A New Criterion for the Stabilization Diagram Used with Stochastic Subspace Identification Methods: An Application to an Aircraft Skeleton - E. Mrabet; M. Abdelghani; N. Ben Kahla (Shock and Vibration)
The modal parameters of a structure that is estimated from ambient vibration measurements are always subject to bias and variance errors. Accordingly the concept of the stabilization diagram is introduced to help users identify the correct model. One of the most important problems using this diagram is the appearance of spurious modes that should be discriminated to simplify modes selections. This study presents a new stabilization criterion obtained through a novel numerical implementation of the stabilization diagram and the discussion of model validation employing the power spectral density. As an application, an aircraft skeleton is used.